Material artifacts of Sundanese looms bearing Nyai Pohaci in the story of the Lutung Kasarung pantun - Retty Isnendes (Universitas Pendidikan Indonesia, 2023)
The present research is motivated by an examination of the intimate link between women, looms, and woven products. In ancient and traditional Sundanese cosmology, the loom is regarded as Nyai Pohaci's embodiment (the Goddess of Rice). It is not, therefore, unexpected that women and looms are intertwined. Even when looms are no longer employed, woven clothes should be present at Sundanese offerings. This study seeks to highlight, analyze, and compare the material artifacts that accompany Sundanese verbal objects in the Lutung Kasarung pantun. The artifacts consist of Sundanese weaving-specific idioms and lexicon. The source of the artifacts is the old Sundanese story of Lutung Kasarung, which offers information about human activities at the time. In this narrative, linguistic artifacts are juxtaposed with visual material artifacts that are now infrequently used or unknown. The study method employs descriptive comparative data gathering techniques with purposeful sampling, as well as visual comparative analytical data processing techniques. Findings reveal that: (1) the linguistic and visual artifacts of looms are classified into three usage categories: (a) spinning cotton into yarn, (b) preparing yarn for weaving, and (c) weaving yarn into cloth; (2) compared to the modern Baduy looms (pakara tinun), the linguistic and material relics are distinct and far less well-known among the population; and (3) in cultural interpretation, the loom becomes a symbol of Nyai Pohaci's sacrifice of her body for human wellbeing in the natural world and of Sundanese women's determination to settle down. In conclusion, there is a dialectical link between linguistic and visual material artifact comprehension.